Creating space for social sustainability through ecological livable at Taman Tasik Cyberjaya, Selangor / Nurshahira Azmin - Azmin, Nurshahira (2017)
Open space provides recreational space for people and enhance the aesthetical and environmental quality of the area. Ecological life is important for human for well-being and need to preserve. This study is to create a space for social sustainability through ecological livable at Taman Tasik Cyberjaya, Selangor. Taman Tasik Cyberjaya has potential to develop more recreational space for user on undeveloped area by using the existing flora and fau na to create the forest concept. The data were collected and analysed to identify the issues and potential of the area. Then the final of this study will come out with new master plan development, which consists of design and approach to achieve the design goal. There needs some approach to implement this study. This study is for create the strategies to integrating the social space with ecological environment.